The New Covenant at Qumran - Andreas Hauw (Sekolah Tinggi Teologi Satyabhakti, Malang)
This paper discusses what the community at Qumran thought about a new covenant. It covers three manuscripts (Temple Scrolls [11Q19], The Rule of the Community [1QS, 4Q255-264a, 5Q11, 5Q13] and The Damascus Document [4Q266-273, 5Q12, 6Q15]) because they use the phrase “new covenant” and present ideas about this covenant. The proper contexts of the three aforementioned manuscripts, and the phrase “new covenant” found in the OT only once(Jer.31:31), including their theological, political and social values are discussed. In addition, the emphasis on the concept of covenant in each manuscript and how it relates them to each other is explained. This paper concludes that the Qumran community reinterpreted the concept of covenant in a new way influenced by the theological, political and social issues of its time.